Upgrading Mekarsari TPS to TPST by Using a Waste Processing Machine for Ngingas Makmur Abadi BUMDes Products - Lissa Rosdiana Noer; Gogor Arif Handiwibowo (IPTEK Journal of Proceedings Series, 2023)
Environmentally friendly waste processing is the process of separating waste with categories of hazardous, toxic, economic value to non-economic value. Meanwhile, the community-based management system involves community participation in the process of sorting, reducing, utilizing and handling the waste. Until 2019, the waste production of the people of Sidoarjo Regency reached around 4,700 m3 per day. However, the ability to transport waste to the Final Disposal Site is only capable of 25%. As a result of the remaining waste that is not transported, the community manages the waste by ignoring environmental procedures, such as throwing it into the river, burning it, putting it in a hole in the ground and so on. In fact, it is possible that the waste contains materials that cannot be decomposed by the environment and even toxic and hazardous materials (B3). Sidoarjo Regency has one of the Integrated Waste Disposal Sites (TPST) named Mekarsari. TPST Mekarsari has 1 unit of plastic waste sorting machine, 1 unit of organic waste chopper and 1 unit of incinerator. However, the current management of the Mekarsari TPST is still not optimal. Some of the things that cause this include the lack of equipment for waste management. Some of the handling of waste that has not been realized include the management of plastic waste mixed with other waste such as packaging plastic bags and small plastics and the handling of organic waste using BSF (Black Soldier Fly) maggots. The solution provided by the ITS Abdimas Team with BUMDes Ngingas Makmur Abadi is to make a study document on the potential development of waste management, study the need for tools/machines for waste management, and procure tools/machines for waste management at the Mekarsari TPST.